Modern ideas about the formation of geological and morphological features of the surface shell of the planet - Yesypovych, Stanislav (Scientific Centre for Aerospace Research of the Earth Institute of Geological Science National Academy of Sciences of Ukraine, Kyiv, Ukraine, 2017)
Hypothesis considered hypothetical logical chain of events or processes, which are based on at least one scientific fact. Consistently filled with facts and theoretical calculations, it can develop into a concept, and then to the theory. Based only on the established fact “spreading” and using a hypothetical concept of “subduction” Plate tectonics is only an interesting hypoth esis, as well, and the action of waves of “dark matter” in the Cosmos stationary objects (ie the existence of “TM” proven, but that apply it in the form of waves — then questions).